The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pssr.201409100
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure chemical vapor deposition (APCVD) grown bi‐layer graphene transistor characteristics at high temperature

Abstract: 1 Introduction Wide band gap semiconductors like gallium nitride (GaN) and silicon carbide (SiC) are currently employed in high temperature power transistor applications owing to their superior combination of characteristics including mobility, breakdown voltage, cutoff frequency, and operating temperature [1]. However, fabricating these devices using high vacuum epitaxial growth techniques (i.e. molecular beam epitaxy, MBE or metal organic chemical vapor deposition, MOCVD) is often cost prohibitive. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…The observation of the σ 2D minimum indicates an existence of the charge neutral point, namely, the Dirac point in the graphene transistors. Such behavior is consistent with that reported for single-layer graphene transistors 32 33 . We define the V G at the charge neutral point as V CNP .…”
supporting
confidence: 92%
“…The observation of the σ 2D minimum indicates an existence of the charge neutral point, namely, the Dirac point in the graphene transistors. Such behavior is consistent with that reported for single-layer graphene transistors 32 33 . We define the V G at the charge neutral point as V CNP .…”
supporting
confidence: 92%
“…[63,93] APCVD-based bilayer graphene growth is another great issue for optimum electronic and photonic devices because of higher carrier mobility and wider band gap by perpendicular electric field compared with single-layer graphene. [102,103] The synthesis of bilayer graphene faced many drawbacks owing to limited grain size and nonsynchronic growth between the first and the second graphene layer. In 2016, Sun et al reported a cooling-APCVD to growth of bilayer graphene on polycrystalline Cu (Figure 10).…”
Section: Figure 8hmentioning
confidence: 99%
“…Among the different synthesis routes, CVD has gained popularity for the production of graphene due to its economical and scalable approach along with its compatibility with current silicon technology. Many researchers have employed atmospheric/ambient pressure CVD to synthesize graphene using either Cu [11][12][13] or Ni [14][15][16][17] as a catalyst. The Ni-catalysed atmospheric pressure chemical vapour deposition (APCVD) synthesis of graphene generally employed either single or polycrystalline Ni thin films deposited on a suitable substrate.…”
Section: Introductionmentioning
confidence: 99%